The effects of capital structure on the financial performance of publicly listed commercial banks: Evidence from the ASEAN-5 countries - Atienza, Ricardo Raphael Alday (Animo Repository, 2021)
Financial performance of commercial banks can be affected by numerous factors, such as capital structure. This study recognizes the importance commercial banks possess with regards to an industry-wide scale and a macroeconomic scale, which is why the researchers aspire to determine which capital structure variables or ratios have cause-and-effect relationships with financial performance ratios to aid management in making decisions. The sample size and setting employed in this study are 35 publicly listed commercial banks in ASEAN-5 countries, namely Indonesia, Malaysia, Philippines, Singapore and Thailand, during the years 2015-2019. The independent variables, namely Short-term debt obligation to total assets (STDTA), Long-Term Debt Obligation to Total Assets (LTDTA), Total Debt Obligation to Total Assets (TDTA), Total Capital Adequacy Ratio (CAR), Tier 1 Capital Ratio, Common Equity Tier 1 (CET1) Ratio, and Loan to Deposit Ratio (LDR), will be empirically tested through Panel Data Regression Analysis to see if they have a positive, negative or no significant relationship with dependent variables such as Return on Equity, Earnings per Share, Net Interest Margin, and Firm Value. Additionally, Inflation, Economic Growth, Liquidity, Growth Opportunities will serve as control variables. Results showed that STDTA and LDR have significant negative effects on financial performance measured by NIM, which means they have inverse relationships with NIM. Moreover, both GOP and RGDP had significant negative effects on their FV. Whereas only the GOP had a negative significant effect on ROE.